Teachers about children left behind raised by grandparents. A qualitative study - Costin, Alina (Technium Social Sciences Journal, 2025)
With the intensification of migration, the number of left-behind children placed in extended families has also increased, and the phenomenon is considered to have significant consequences on children’s well-being (Ratha, Mohapatra, Scheja, 2011; Sănduleasa, Matei, 2015). Grandparents with custody have become an alternative family structure (Edwards, Rothbard, 2000) frequently encountered in Romania, which is why it is essential to understand the implications of this special situation. In this qualitative study, we conducted two focus groups, each with eight participants—teachers of middle school students—with whom we discussed the difficulties faced at school by children raised by their grandparents. The thematic analysis revealed four main themes: (1) behavioral disorders, (2) stress and anxiety, (3) responsibility and maturity, and (4) vulnerability. Participants reported that these children stand out very clearly among their peers and that, depending on the family context, they either develop responsibility and maturity or become antisocial and rebellious. These findings have implications for including them in a risk category and implementing support programs for grandparents who take on the responsibility of raising them.